Study of Natural products Adverse Reactions (SONAR) in children seen in mental health clinics: a cross-sectional study - Sunita Vohra; Liliane Zorzela; Emma Sparks; Candace Necyk; Baljit Khamba; Liana Urichuk; Joanne Barnes (BMJ Paediatrics Open)
Background Paediatric mental health patients frequently use natural health products (NHP) in addition to prescription medications, but very little is known about adverse events and possible NHP–drug interactions.Objective To determine: (1) the prevalence of paediatric mental health patients taking prescription medications only, NHP only, both NHP and prescription medications concurrently or neither; (2) which prescription medications and NHP are most commonly used in paediatric mental health populations and (3) adverse events experienced in the last 30 days (serious and non-serious).Design Cross-sectional surveillance study.Setting Paediatric mental health clinics.Population/intervention On their first clinic visit, paediatric mental health patients were provided with a form inquiring about prescription drug use, NHP use and any undesirable event experienced in the last month.Results Of the 536 patients included in this study, 23% (n=120) reported taking only prescription medication(s), 21% (n=109) reported only NHP use, 21% (n=112) reported using both NHP and prescription drugs concurrently, and 36% (n=191) reported using neither. Overall, there were 23 adverse events reported; this represents 6.3%, 2.8%, 10.8% and 0.6% of each population, respectively. The majority of patients who experienced an adverse event reported taking more than one NHP or prescription drug. No serious adverse events were reported.Conclusion Nearly half of the paediatric mental health patients in this study were taking NHPs alone or in addition to prescription medications. Active surveillance identified multiple adverse events associated with NHP and prescription drug use; none were serious. Healthcare professionals were encouraged to initiate conversations regarding NHP use.